Теорія політичного вибору як складова ліберальної доктрини - Константинова, Т. В.; Константинова, Т. В.; Konstantinova, Т. (My University, 2013)
The paper analyzes the theory of political choice, which was formed in the doctrines of liberalism. Determined that at present the political choice is analyzed from the standpoint of rational choice theory and social weighty choice. The interpretation of political choice from the standpoint of political philosophy (A. de Tocqueville, I. Berlin) and economic theory (K. Arow, J. Buchanan) are examined.
Константинова Т. В. Теорія політичного вибору як складова ліберальної доктрини / Т. В. Константинова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 58-66.
Keywords: теорія політичного вибору; ідеологічна доктрина лібералізму; теорія раціонального вибору; теорія суспільно вагомого вибору; політична філософія; теория политического выбора; идеологическая доктрина либерализма; теория рационального выбора; теория общественно весомого выбора; политическая философия; theory of political choice; ideological doctrine of liberalism; rational choice theory; theory of public choice weighty; political philosophy